Shiva baby [videorecording (Blu-Ray)] - Seligman, Emma (Film director); Sennott, Rachel; Gordon, Molly, 1994-; Draper, Polly, 1956-; Deferrari, Danny; Melamed, Fred, 1956-; Agron, Dianna, 1986-; Marx, Ariel, 1988- (Utopia Select, LLC, 2021)
Attending a family shiva with her parents, college student Danielle gets quizzed about her life and future plans by various relatives, encounters her ex-girlfriend Maya as well as her sugar daddy Max, his wife Kim and their baby.